Igangværende receptionsforskning - Buhl, Clau; Drotner, Kirsten; Jerslev, Anne; Lehrmann, Ulrik; Rasmussen, Tove Arendt; Tufte, Birgitte (MedieKultur: Journal of media and communication research, 1988)
Igangværende receptionsforskning